Emotion and Meaning in Music - Meyer, Leonard B. (, IL University of Chicago Press, 1961)
Altogether it is a book that should be required reading for any student of music, be he composer, performer, or theorist. It clears the air of many confused notions . . . and lays the groundwork for exhaustive study of the basic problem of music theory and aesthetics, the relationship between pattern and meaning."?David Kraehenbuehl, Journal of Music Theory "This is the best study of its kind to have come to the attention of this reviewer."?Jules Wolffers, The Christian Science Monitor"It is not too much to say that his approach provides a basis for the meaningful discussion of emotion and meaning in all art."?David P. McAllester, American Anthropologist"A book which should be read by all who want deeper insights into music listening, performing, and composing."?
Keywords: Music philosophy and esthetics; Semiotics; Hermeneutics; Emotion